2016
DOI: 10.1016/j.chom.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR Complex Controls HIV Latency

Abstract: SUMMARY A population of CD4 T lymphocytes harboring latent HIV genomes can persist in patients on antiretroviral therapy, posing a barrier to HIV eradication. To examine cellular complexes controlling HIV latency, we conducted a genome-wide screen with a pooled ultracomplex shRNA library and in vitro system modeling HIV latency and identified the mTOR complex as a modulator of HIV latency. Knockdown of mTOR complex subunits or pharmacological inhibition of mTOR activity suppresses reversal of latency in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
197
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(216 citation statements)
references
References 58 publications
(76 reference statements)
12
197
0
Order By: Relevance
“…In addition, Martin et al reported on the potential beneficial use of rapamycin in the context of HIV "shock-and-kill" strategies (87). These two reports (86,87) further support the conclusions of our current study, which reveals the key role played by mTOR in regulating multiple postentry and postintegration HIV replication steps in gut-homing Th17-polarized CCR6 + T cells. In conclusion, our findings point to CCR6 as a "zip code" molecule expressed on the surface of CD4 + T cells transcriptionally programmed to become HIV targets upon recruitment into the intestine and provide a detailed molecular explanation for preferential HIV/SIV replication and persistence in gut-homing CCR6 + CD4 + T cells (24,25,37,42).…”
Section: On Hiv Replication In Ccr6supporting
confidence: 89%
See 1 more Smart Citation
“…In addition, Martin et al reported on the potential beneficial use of rapamycin in the context of HIV "shock-and-kill" strategies (87). These two reports (86,87) further support the conclusions of our current study, which reveals the key role played by mTOR in regulating multiple postentry and postintegration HIV replication steps in gut-homing Th17-polarized CCR6 + T cells. In conclusion, our findings point to CCR6 as a "zip code" molecule expressed on the surface of CD4 + T cells transcriptionally programmed to become HIV targets upon recruitment into the intestine and provide a detailed molecular explanation for preferential HIV/SIV replication and persistence in gut-homing CCR6 + CD4 + T cells (24,25,37,42).…”
Section: On Hiv Replication In Ccr6supporting
confidence: 89%
“…In line with our recent report that HIV DNA persists in colon-infiltrating CCR6 + T cells during ART (37), it remains to be determined whether mTOR expression identifies a fraction of CCR6 + T cells enriched in HIV DNA and whether mTOR activation contributes to residual HIV replication in colon-infiltrating CCR6 + T cells during ART. While this manuscript was in preparation for submission, Besnard et al reported the results of a shR-NA screen that revealed mTOR as a regulator of HIV latency (86) via mechanisms involving CDK9 and NF-κB activation that controls Tat-dependent HIV transcription (86). In addition, Martin et al reported on the potential beneficial use of rapamycin in the context of HIV "shock-and-kill" strategies (87).…”
Section: On Hiv Replication In Ccr6mentioning
confidence: 99%
“…The Ser-Thr kinase mTOR complexes 1 and 2 were reported as a possible pathway for latency reversal [126]. Other well-known complexes implicated in the latency process were identified such as P-TEFb and the silencing complex PRC2 (EED, EZH2 and YY1 subunits), validating the shRNA screen approach [23].…”
Section: Host Factors Influencing Hiv-1 Latencymentioning
confidence: 86%
“…Other well-known complexes implicated in the latency process were identified such as P-TEFb and the silencing complex PRC2 (EED, EZH2 and YY1 subunits), validating the shRNA screen approach [23]. The authors used CRISPR interference to mTOR subunits, and specific small molecule inhibitors, to demonstrate the role of mTOR complexes in latency reversal [126]. Decrease in mTOR expression or reduced kinase activity impaired LRA-mediated or antigenic HIV-1 transcriptional activation, in latent cell line models and in primary CD4+ T lymphocytes isolated from ART-treated infected individuals.…”
Section: Host Factors Influencing Hiv-1 Latencymentioning
confidence: 97%
See 1 more Smart Citation